The Health Returns of Education Policies from Preschool to High School and Beyond - Johnson, Rucker C (American Economic Review, 2010)
The accessibility of quality schools and educational resources for children are key engines of upward mobility in the United States, holding the potential to break the cycle of poverty from one generation to the next. Inequalities in economic status tend to be correlated across generations in part because of intergenerational correlations in health and education (Rucker C. Johnson 2009). Residential segregation by race and class that leads to unequal access to quality schools is often cited as a culprit in perpetuating inequality in attainment outcomes. Over the past four decades, three major government interventions have had substantial impacts on the provision of school resources and have narrowed black-white differences in access to dimensions of school quality: i) court-mandated school desegregation, ii) state legislation and legal action aimed to change the distribution and level of school funding, and iii) the expansion of targeted preschool programs for disadvantaged children through Head Start. Court ordered school desegregation has been described as the most controversial and ambitious social experiment of the past 50 years. Human Capital, HealtH OutCOmes, and inequality †